Uji Mutagenik β-Karoten Alga Merah Rhodymenia Pseudopalmata terhadap Mencit Jantan Galur Balb/C yang Diinduksi 7,12-Dimetilbenzen (A)Antrasen (DMBA) - Christina Astutiningsih; Leenawaty Limantara; Ocky K. Radjasa (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2010)
Carotenoids are important biological compounds in cancer prevention because theycan inhibit the formation of free radicals, which react directly with oxygen. This researchwas aimed to determine the effect of antimutagenic â-carotene on 7.12-dimetilbenz(a)antracene (DMBA)-induced mice. From the observation of the mortality rate during theresearch period, the DMBA group showed the highest rate of mortality compared to thecontrol group and the groups of â-carotene isolates. The incidence of tumors showed thedeclining trend in the groups of test animals that were given with the increasing dosesof β-caroten isolate, i.e. 1.82; 3.64 and 7.28 mg kg-1 BW. The result may be caused bythe increasingly high levels of â-carotene in the test solutions, resulting in the lowertissue damage and the inhibited growth of tumors in the lungs. Based on Kruskal-Wallisstatistical analysis conducted on lung histology observational data for ten samples ofeach treatment group, it was confi rmed that there were signifi cant differences betweentreatments, which mean that â-carotene isolates can inhibit cancer growth in lung andskin of DMBA-induced animals.Keywords: β-carotene isolate, antimutagenic, DMBA (7,12-dimetilbenz(a)antracene)